Proposal to improve the maintenance system in telescopic cranes based on preventive maintenance to reduce costs - Guzman Pipa, Manuel (2025)
The main objective of this research was to implement an improvement in the maintenance system of a company, to reduce these costs and increase the useful life of the machines because they exceed the established budget (9.12% compared to the 6% budgeted). To achieve this, a maintenance plan was proposed based on the RCM (Reliability Centered Maintenance) methodology, taking a telescopic crane as a sample to demonstrate potential improvements in both the crane's performance and the efficiency of the company in general. After the application, maintenance costs were reduced from 9.12% to 8%, which represents an improvement of 24.13%. In addition, a significant decrease in the average failure rate was observed by 21.54%. Crane availability also improved 19.7%. Finally, the Mean Time Between Stops (MTBS) improved by 41.2%, demonstrating that the implementation of the improvement proposal has been highly favorable for the company.